Transformation of Erythrocytes During Cryopreservation with Oxyethylated Glycerol Derivatives with n=25 and n=30 Polymerization Degree - Pakhomova, Yulia S.; Kompaniets, Antonina M.; Kuleshova, Larysa G. (Problems of Cryobiology and Cryomedicine, 2016)
This paper presents experimental data on the effect of oxyethylated glycerol derivatives with n=25 and n=30 polymerization degree (OEGn=25 and OEGn=30) on shape and diameter of human erythrocytes at the stages of cryopreservation. The shape and diameter of the cells before and after cryopreservation were studied in ‘live drop’ by means of immersion microscopy. It has been shown that the contact with the investigated cryoprotective solutions and following low temperature preservation led to erythrocyte transformation. Character of change in their shape and diameter before and after cryopreservation depended upon the polymerization degree and concentration of cryoprotectant. It was established that 40% OEGn=25 and OEGn=30 solutions at the exposure stage caused cell deformation and agglutination. The largest number of erythrocytes of discoid shape was maintained after cryopreservation in 30% OEGn=25 and OEGn=30 solutions. It was found that after cooling-warming the cells in 30% OEGn=30 solution their diameter increased, while using 30% concentration of OEGn=25 this parameter was within the normal range. Probl Cryobiol Cryomed 2016; 26(4): 349–360